SAFI MUSTAFA’S POEM RELATED TO DISCOURSING WITH HIS HEART - Ahmet DOĞAN (Fırat University, 2019)
Safi Mustafa who is one of the poets classical Turk literature in 18th century has not mentioned in collection in biographies. He has got a